Voices from Larung Gar shaping Tibetan Buddhism for the twenty-first century - Gayley, Holly (Boulder, Colorado Snow Lion Publications, an imprint of Shambhala Publications, Inc, 2021)
"An anthology of modern Buddhist writings from practitioners and teachers in Larung Gar, Tibet"--
Literaturverzeichnis: Seite 257-269 und Index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Buddhism -- China -- Tibet Autonomous Region; Aufsatzsammlung